Prenatal exposure to methyl mercury from fish consumption and polyunsaturated fatty acids: associations with child development at 20 mo of age in an observational study in the Republic of Seychelles–. Issue 3 (21st January 2015) - Strain, JJ; Yeates, Alison J; van Wijngaarden, Edwin; Thurston, Sally W; Mulhern, Maria S; McSorley, Emeir M; Watson, Gene E; Love, Tanzy M; Smith, Tristram H; Yost, Kelley; Harrington, Donald; Shamlaye, Conrad F; et al.
ABSTRACT: Background: Fish is a rich source of n–3 polyunsaturated fatty acids (PUFAs) but also contains the neurotoxicant methyl mercury (MeHg). PUFAs may modify the relation between prenatal MeHg exposure and child development either directly by enhancing neurodevelopment or indirectly through the inflammatory milieu. Objective: The objective was to investigate the associations of prenatal MeHg exposure and maternal PUFA status with child development at 20 mo of age. Design: The Seychelles Child Development Study Nutrition Cohort 2 is an observational study in the Republic of Seychelles, a high-fish-eating population. Mothers were enrolled during pregnancy and their children evaluated at 20 mo of age by using the Bayley Scales of Infant Development II (BSID-II), the MacArthur Bates Communicative Development Inventories (CDI), and the Infant Behavior Questionnaire–Revised. There were 1265 mother-child pairs with complete data. Results: Prenatal MeHg exposure had no direct associations with neurodevelopmental outcomes. Significant interactions were found between MeHg and PUFAs on the Psychomotor Developmental Index (PDI) of the BSID-II. Increasing MeHg was associated with lower PDI but only in children of mothers with higher n–6/n–3. Among mothers with higher n–3 PUFAs, increasing MeHg was associated with improved PDI. Higher maternal docosahexaenoic acid (DHA) was associated with improved CDI total gestures (language development) but was significantly adversely associated with the Mental Development Index (MDI), both with and without MeHg adjustment. Higher n–6:n–3 ratios were associated with poorer scores on all 3 CDI outcomes. Conclusions: We found no overall adverse association between prenatal MeHg exposure and neurodevelopmental outcomes. However, maternal PUFA status as a putative marker of the inflammatory milieu appeared to modify the associations of prenatal MeHg exposure with the PDI. Increasing DHA status was positively associated with language development yet negatively associated with the MDI. These findings may indicate the existence of an optimal DHA balance with respect to arachidonic acid for different aspects of neurodevelopment.